Massive vector particles tunneling from Kerr and Kerr–Newman black holes - Li, Xiang-Qian; Chen, Ge-Rui (Physics letters. B, 2015)
In this paper, we investigate the Hawking radiation of massive spin-1 particles from 4-dimensional Kerr and Kerr–Newman black holes. By applying the Hamilton–Jacobi ansatz and the WKB approximation to the field equations of the massive bosons in Kerr and Kerr–Newman space-time, the quantum tunneling method is successfully implemented. As a result, we obtain the tunneling rate of the emitted vector particles and recover the standard Hawking temperature of both the two black holes.